EVOLUSI STANDAR AKUNTANSI KEUANGAN BERBASIS IFRS DAN IMPLIKASINYA TERHADAP KUALITAS INFORMASI AKUNTANSI: TINJAUAN LITERATUR 2015-2025 - Sadiqin, Amin (Penerbit Lafadz Jaya, 2025)
This research analyzes the evolution of IFRS-based financial accounting standards in Indonesia and their implications for accounting information quality during the 2015-2025 period. Using a qualitative approach through comprehensive literature review, the research evaluates the trajectory of IFRS convergence that has moved from initial adoption to full integration. The analysis shows that IFRS implementation has contributed to improving dimensions of accounting information quality, particularly in terms of relevance, comparability, and earnings management reduction. However, its effectiveness is strongly influenced by contextual factors such as legal systems, human resource capacity, sectoral regulations, and entity characteristics. This study identifies three stages in the evolution of IFRS-based accounting standards in Indonesia: initial adoption (2015-2018), consolidation and adjustment (2019-2022), and full integration (2023-2025). Contemporary challenges in implementation include economic digitalization, integration of sustainability reporting, and implementation gaps between large entities and SMEs. This research contributes to the literature by chronologically and thematically mapping the development of IFRS-based accounting standards in Indonesia, as well as identifying areas requiring attention from regulators, practitioners, and academics. Future prospects will depend on the ability to balance compliance with global standards with specific domestic market needs and strengthening supervisory infrastructure.